2019
DOI: 10.3390/antiox8110539
|View full text |Cite
|
Sign up to set email alerts
|

Specific Activity of Superoxide Dismutase in Stallion Seminal Plasma Is Related to Sperm Cryotolerance

Abstract: While the removal of seminal plasma is a routine practice prior to equine sperm cryopreservation, this fluid contains the main source of antioxidant enzymes able to scavenge these reactive oxygen species. Therefore, stallion seminal plasma components may have an impact on ejaculate freezability. Against this background, this study was designed to investigate whether the activities of the main stallion seminal plasma antioxidant enzymes are related to sperm cryotolerance. With this purpose, 16 ejaculates were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(73 citation statements)
references
References 47 publications
(65 reference statements)
7
54
1
2
Order By: Relevance
“…For this reason, there is intense interest in the use of antioxidants to promote cryosurvival. Recent studies have, for example, indicated that the specific activity of SOD in seminal plasma is related to the freezability of stallion, jackass and dog spermatozoa [74,75]. Loss of SOD from human semen samples is also thought to be a key factor in determining their ability to survive cryostorage [76].…”
Section: Cryostoragementioning
confidence: 99%
“…For this reason, there is intense interest in the use of antioxidants to promote cryosurvival. Recent studies have, for example, indicated that the specific activity of SOD in seminal plasma is related to the freezability of stallion, jackass and dog spermatozoa [74,75]. Loss of SOD from human semen samples is also thought to be a key factor in determining their ability to survive cryostorage [76].…”
Section: Cryostoragementioning
confidence: 99%
“…Some studies have demonstrated that superoxide dismutase 1 is tightly associated with sperm quality, including sperm motility 38 40 . In some previous studies, superoxide dismutase was found to exist in seminal plasma, and may be associated with sperm fertility and cryotolerance 41 , 42 . But, in this study, superoxide dismutase 1 was found to be more abundant in the low motility group.…”
Section: Discussionmentioning
confidence: 90%
“…Herein, the observed reduction in oxidative stress by the application of quercetin in dog sperm coincides with the results found in the rats, Red Jungle fowl and the roosters where supplementation with quercetin reduced oxidative stress (Naja et al 2020, Rakha et al 2020, Yelumalai et al 2019). The mechanism employed by quercetin to ameliorate oxidative stress in post-thaw sperm is thought to occur via an increase in the sperm total antioxidant capacity and the amelioration of lipid peroxidation (Papas et al 2019). Quercetin has also caused improvements in advanced DNA integrity, owing to reduced ROS levels, as reported in bulls (Avdatek et al 2018), which could have contributed to fertility.…”
Section: Discussionmentioning
confidence: 99%
“…In sperm cryopreservation, due to discarding the seminal plasma, sperms lack essential antioxidants that defeat ROS (Kashou et al 2013), and further oxidative stress develops, which potentiates cryo-induced stress, damage, and subsequent apoptosis (Fraser et al 2011, Iwasaki &Gagnon 1992, Papas et al 2019). The cryopreservation of cells promotes the oxidation of phospholipids in the cell membrane, increases intracellular ROS, and thus leads to DNA fragmentation and cell membrane damage (El- Said et al 2014, Su et al 2019).…”
Section: Introductionmentioning
confidence: 99%